Bound-state solutions of the two-dimensional Dirac equation with Aharonov–Bohm-Coulomb interaction in the presence of extended uncertainty principle. (30th September 2020) - Hamil, B; Merad, M; Birkandan, T
Abstract: The Dirac equation in the presence of Aharonov–Bohm-Coulomb interaction is studied in the framework of the extended uncertainty principle. The equation governing the dynamics of the system is reduced to a differential equation which is solved in terms of the hypergeometric functions as the wave functions of the system. Expressions for the bound-state energies are also obtained analytically. A brief graphical evaluation of our results is also presented.